2007
DOI: 10.1097/01.ta.0000229814.08289.9a
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Trauma From Recreational All-Terrain Vehicle Use in Central Kentucky: A 6-Year Review

Abstract: Almost half of all patients sustained one fracture or joint dislocation with the spine being the most prevalent location. Injury severity, the low number referred to rehabilitation facilities, and predominantly rural residence locations suggests that many may not be accessing needed healthcare services. Prospective longitudinal outcome studies are needed to assess patient functional independence, quality of life, and health care system effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…This percentage is similar to previous studies; however, we found a higher ratio of upper extremity injuries than previously reported. 4,10 We found that the lower extremity and spine typically sustained more severe injuries. One previous study did not include patients who were admitted for less than 2 days.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This percentage is similar to previous studies; however, we found a higher ratio of upper extremity injuries than previously reported. 4,10 We found that the lower extremity and spine typically sustained more severe injuries. One previous study did not include patients who were admitted for less than 2 days.…”
Section: Discussionmentioning
confidence: 97%
“…It is estimated that 7.8 million ATVs are now in use throughout the United States. 1,3,4 The popularity and potentially devastating effects of ATVs are more evident in rural settings. The Consumer Product Safety Commission estimated that 60% of all ATVrelated injuries occur in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…5,15 It has been reported that loss of consciousness occurs in over half of ATV related injuries. 7 Almost one third of head injuries involved skull fractures and CT imaging demonstrated significant intracranial haemorrhage in one fifth of these head injury patients. 16 While Fig.…”
Section: Head Injurymentioning
confidence: 99%
“…3,5,6 Risk factors for ATV related injury and death include male sex, age <18, white race, rural residence, intoxication, driving inexperience, recreational use of ATV as opposed to work related usage and large engine size. 7 Large engine ATV production has increased threefold since 2003. 8 These large engine vehicles can reach speeds of up to 120 km per hour and may weigh in excess of 230 kg.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation